2020
DOI: 10.1101/2020.05.28.113522
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sox9EGFPdefines biliary epithelial heterogeneity downstream of Yap activity

Abstract: Intrahepatic bile ducts are lined by biliary epithelial cells (BECs). However, defining the genetic heterogeneity of BECs remains challenging, and tools for identifying BEC subpopulations are limited. Here, we characterize Sox9EGFP transgene expression in the liver and demonstrate that GFP expression levels are associated with distinct cell types. BECs express “low” or “high” levels of GFP, while periportal hepatocytes express “sublow” GFP. Sox9EGFP distribution varies by duct size, with GFPhigh BECs found at … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…1B‐D)—which aligns with Tulasi’s finding based on SOX9 (SRY [sex determining region Y]‐box 9) immunofluorescent staining, reflecting the heterogeneity of their intrahepatic localization and regeneration capacity. ( 19 )…”
Section: Resultsmentioning
confidence: 99%
“…1B‐D)—which aligns with Tulasi’s finding based on SOX9 (SRY [sex determining region Y]‐box 9) immunofluorescent staining, reflecting the heterogeneity of their intrahepatic localization and regeneration capacity. ( 19 )…”
Section: Resultsmentioning
confidence: 99%
“…22 Interestingly, another recent study demonstrated distinct Sox9 EGFP expression levels at the different anatomical sites of the biliary tree. 31 BECs from different regions (IHBDs, common bile duct, and gallbladder) express regional-specific markers, such as SOX4 expression in intrahepatic BECs, trefoil factor 2 in extrahepatic BECs, and SOX17 in gallbladder BECs. 32 33 Following organoid culture, BECs from different regions exhibited similar transcriptional signatures, suggesting a partial loss of their regionalization.…”
Section: Architecture and Regional Diversity In The Biliary Treementioning
confidence: 99%